2018
DOI: 10.1002/naaq.10072
|View full text |Cite
|
Sign up to set email alerts
|

Transport Stress Mitigation and the Effects of Preanesthesia on Striped Bass

Abstract: The demand for Striped Bass Morone saxatilis as food and sport fish has generated interest in developing effective transport and handling protocols. Studies have shown that anesthetics and elevated salinity can reduce transport stress in Striped Bass, but no studies have compared stress responses among strains or compared and combined treatments to maximize efficacy. In this study, 1‐h transport trials were conducted with subadults produced from wild‐caught (Florida strain) and domesticated Striped Bass. Fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…Many studies emphasize the physiological stress responses and their consequences induced by the common transport procedures. The use of anesthetics is a relatively new research subject in live-fish transport, with the use of MS-222 potentially compromising the health of fish species such as crucian carp ( Carassius auratus ) [ 19 ], gilthead sea bream ( Sparus aurata ) [ 20 ] and striped bass ( Morone saxatilis ) [ 21 ]. Yet, anesthetics induce species-specific responses [ 18 ] that require further tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies emphasize the physiological stress responses and their consequences induced by the common transport procedures. The use of anesthetics is a relatively new research subject in live-fish transport, with the use of MS-222 potentially compromising the health of fish species such as crucian carp ( Carassius auratus ) [ 19 ], gilthead sea bream ( Sparus aurata ) [ 20 ] and striped bass ( Morone saxatilis ) [ 21 ]. Yet, anesthetics induce species-specific responses [ 18 ] that require further tests.…”
Section: Discussionmentioning
confidence: 99%
“…Among the broad spectrum of fish anesthetics, the most used is tricaine methanesulfonate (MS-222) [ 13 , 14 ], although species differences in pharmacokinetics and pharmacodynamics have been described [ 17 ]. In addition, a report has shown this compound to be aversive to some fish species [ 18 ], and further studies demonstrated that MS-222 might elicit immune-biochemical responses (increased cortisol, altered oxidative status and immune system) in different fish species under transport conditions [ 19 , 20 , 21 ]. In general, MS-222 may compromise the health and welfare of the fish, requiring further studies to better understand how this and other anesthetics affect welfare during fish transport.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research on striped bass and its hybrids has been conducted and entire books (Harrell, 1997) and culture method guidelines have been published (Bonn et al, 1976;Harrell et al, 1990). In addition, many studies focusing on striped bass nutrition (Gatlin III, 1997;Small & Soares Jr, 1998;Small, Soares Jr., & Woods III, 2000;Webster & Lovell, 1990;Woods III & Soares Jr., 1996), health (Harms, Sullivan, Hodson, & Stotskopf, 1996;Noga, Kerby, King, Aucoin, & Giesbrecht, 1994;Noga, Wang, Grindem, & Avtalion, 1999;Plumb, 1997;Salger, Reading, & Noga, 2017), pond and recirculating aquaculture system (RAS) culture methodologies (Geiger & Turner, 1990;Geiger, Turner, Fitzmayer, & Nichols, 1985;Harrell, 1997;McGinty & Hodson, 2008;Turano, Borski, & Daniels, 2008), pond fingerling production (Ludwig, 1999(Ludwig, , 2004Ludwig, Perschbacher, & Edziyie, 2010;Ludwig & Tackett, 1991), fingerling production in biofloc production systems (Green, Rawles, Webster, & McEntire, 2018), stress mitigation (Harrell, 1992;Harrell & Moline, 1992;Kenter, Gunn, & Berlinsky, 2019) Borski, 2004) have been published and are well known. Therefore, the ability to culture these fish in numerous environments on an experimental scale is not in question and, importantly, the wealth of studies conducted on striped bass has allowed for the development of a captively bred, domesticated broodstock Hallerman, 1994).…”
Section: Striped Bass Culture Methods and Toolsmentioning
confidence: 99%
“…If the adaptive response is successful, a return to pre-stressed conditions (homeostasis) is achieved, but if the stressor is too severe or long-lasting, the coping mechanisms become maladaptive and detrimental to the fish's performance (Barton, 2002;Barton & Iwama, 1991).The common response to stressors (General Adaptation Syndrome (GAS; Selye, 1950Selye, , 1973 in fish and other vertebrates has been well studied and consists initially of neural activation of the hypothalamus-pituitary-interrenal gland (HPI) axis and release of catecholamines, followed by production of the glucocorticoid, cortisol (Mommsen et al, 1999;Wendelaar Bonga, 1997). Elevated circulating cortisol levels have primarily been used as an indicator of aquaculture-induced stress because of its predictive responsiveness and relative ease of measurement (Barton & Iwama, 1991).Correlations between elevated cortisol and long-term performance traits (growth, disease susceptibility), however, are often not evaluated and have been inconsistent when analysed (Kenter et al, 2019).…”
mentioning
confidence: 99%
“…Correlations between elevated cortisol and long-term performance traits (growth, disease susceptibility), however, are often not evaluated and have been inconsistent when analysed (Kenter et al, 2019).…”
mentioning
confidence: 99%